"Said to be a very honest Jew": The R. G. Dun Credit Reports and Jewish Business Activity in Mid-19th Century Montreal - Tulchinsky, Gerald (Urban History Review / Revue d'histoire urbaine, 1990)
This paper examines the participation of members of Montreal's tiny Jewish community in the city's economic development between the 1840's and the 1870's. Based largely on the R. G. Dun & Co. credit reports, this study reveals that Jews concentrated mainly in the retailing of jewellery and fancy goods, tobacco and dry goods and in clothing manufacturing. Most were petty traders; they were often transitory figures who succumbed to the vagaries of business fluctuations, or were incompetent, poorly financed or dishonest. Although his Jewishness was always taken note of, a businessman's creditworthiness was apparently assessed as objectively as that of a non-Jew: there is no evidence that antisemitism - of which there is plenty in these reports - by itself adversely affected Jewish business mobility or success to any significant extent. In this period Jewish businessmen tended to keep to trades or businesses with which they were familiar before immigrating; they often brought inventory with them, relied on family credit and kept largely to themselves. Most achieved a modest living while a few successful tobacco and clothing manufactures emerged.